Searching for potential ice-rich mining sites on the Moon with the Lunar Volatiles Scout. (February 2020) - Biswas, J.; Sheridan, S.; Pitcher, C.; Richter, L.; Reganaz, M.; Barber, S.J.; Reiss, P.
Abstract: Multiple remote observations have indicated the existence of ice deposits in permanently shadowed regions (PSRs) near the lunar poles, nurturing hopes of possible future resource exploitation. However, the interpretation of the orbital data remains ambiguous and ground truth data is necessary for validation. The Lunar Volatiles Scout (LVS) is an integrated instrument for regolith sampling, gas extraction, and analysis that enables mobile prospecting for lunar volatiles, such as loosely adsorbed water and subsurface ice up to a depth of 10 ​cm. This study presents results of breadboarding activities using an integrated prototype of the LVS instrument to investigate soil insertion and to demonstrate gas extraction and analysis in thermal vacuum. The required vertical force for LVS insertion into dry and ice-bearing regolith was determined to be less than 15 ​N and sample-to-sample cross-contamination was found to be negligible. Thermal-vacuum test results proved the successful extraction of water from a hydrated lunar regolith simulant and detection of species across a mass to charge ratio m/z range of 15–200. Highlights: Regolith Sampling, Gas Extraction & Analysis Instrument for Volatiles Exploration. Thermal-Vacuum testing of integrated instrument. Drill testing in icy regolith simulants.